Effect of sparger design on the flow in a bubble column: symbolic analysis of LDA data - Kulkarni, A. A.; Deshpande, Suvarna S.; Joshi, J. B.; Kumar, V. Ravi; Kulkarni, B. D. (Industrial & Engineering Chemistry Research, 2007)
This paper aims at developing a methodology that helps in the characterization of the effects of a single point and multipoint sparger on the flow patterns in a bubble column reactor. The methodology uses the simultaneously measured instantaneous velocity-time data (two orthogonal velocity components) using LDA at different measurement locations. The data sets are transformed into their equivalent description in terms of polar coordinates, viz., resultant velocity vector and angle. This information is further transformed in terms of symbolic representation in a binary number format. The covariance matrices obtained from the binary data are analyzed for their eigenvalues, and the spectrum is used for the identification of the dominant, energy containing modes in the data. In the vicinity of the sparger, the nature of covariance matrix and the eigenvalue spectrum for the single point sparger (SPS) data was significantly different from that of the multipoint sparger (MPS). In the bulk region, for both types of spargers, the nature of the eigenvalues and the number of dominant modes is seen to be different from the near sparger region. In general, more numbers of eigenvalues are required to capture the total energy in the data for a multipoint sparger when compared to a single point sparger. This suggests a higher level of complexities existing due to the intricate hydrodynamics for the multipoint sparger. The possible use of this methodology for practical purposes, e.g., identification of malfunctioning of gas-liquid sparger reactors is discussed.

Hydrodynamics and liquid phase residence time distribution in mesh microreactor - Kulkarni, A. A.; Gorasia, A. K.; Ranade, V. V. (Chemical Engineering Science, 2007)
This paper is focused on the experimental analysis of residence time distribution and phase hold-up in a mesh microreactor. A microreactor, where a finely weaved mesh is sandwiched between two flat plates with specific inlets for gas and liquid, is proposed. The microvolumes formed upon sandwiching the mesh are totally connected and thus it yields a view of several interconnected microvolumes. This system is easy to build and does not need precision micromachining. A high-speed photographic analysis yielded the phase distribution for different mesh types over a wide range of operating gas and liquid flow rates. The RTD was studied by measuring the liquid phase conductivity at the outlet of the reactor. Channeling prevailed for mesh with smaller open area. The ADEM was used for fitting the tracer curves with tailing ends. The RTD and the image analysis for all the mesh types showed hysteresis when the gas flow rate was maintained constant and the liquid flow rate was gradually increased and then decreased. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: hydrodynamics; hysteresis; image analysis; microreactor; residence time distribution

Feasibility studies and dynamics of catalytic liquid phase esterification reactions in a micro plant - Kulkarni, A. A.; Zeyer, K. -P.; Jacobs, T.; Kaspereit, M.; Kienle, Achim (Chemical Engineering Journal, 2008)
We present a new micro reactor concept which is suitable for investigations of heterogeneously catalyzed liquid phase reactions. In the set-up two reactants are mixed in a commercially available interdigital micro mixer. The outlet of the micro mixer is connected to a modular micro reactor that consists of stacked plates. Each plate contains a milled meandering channel filled with catalyst beads. By using a variable number of plates the residence time can be manipulated and thus adjusted for a specific task. The synthesis of butyl acetate is considered as a model reaction since it has been investigated in detail in conventional reaction systems. In a first step, some experimental results of the heterogeneously catalyzed reaction are presented. In the second part, the set-up is operated as a chromatographic reactor. Dynamic behaviour is investigated applying the frontal analysis mode and the elution chromatography mode. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: chromatographic reactor; heterogeneous catalysis; integrated process; modular micro reactor

In situ synthesis of ligand reduced/capped silver nanoparticles and the effect of temperature and ligand structure on the size of silver nanoparticles - Kasture, M. B.; Patel, P.; Prabhune, Asmita; Ramana, C. V.; Kulkarni, A. A.; Bhagavatula L. V. Prasad (Journal of Chemical Sciences, 2008)
We report in situ synthesis of silver nanoparticles using biosurfactants called sophorolipids as reducing and capping agents. We further study the effect of temperature and the structure of sophorolipid on the size of silver nanoparticles obtained. The silver nanoparticles were characterized by UV-visible, transmission electron microscope (TEM) and light scattering (DLS) analysis techniques.
Keywords: dynamic light scattering; Nucleation and growth; silver nanoparticles; Sophorolipid

SVR-based prediction of point gas hold-up for bubble column reactor through recurrence quantification analysis of LDA time-series - Gandhi, Ankit B.; Joshi, J. B.; Kulkarni, A. A.; Jayaraman, Valadi K.; Kulkarni, B. D. (International Journal of Multiphase Flow, 2008)
Recurrence quantification analysis (RQA) has emerged as a useful tool for detecting singularities in nonstationary time-series data. In this paper, we use RQA to analyze the velocity-time data acquired using laser doppler anemometry (LDA) signals in a bubble column reactor for Single point and Multipoint point spargers. The recurring dynamical states within the velocity-time-series occurring due to the bubble and the liquid passage at the point of measurement, are quantified by RQA features (namely % Recurrence, % Determinism, % Laminarity and Entropy), which in turn are regressed using support vector regression (SVR) to predict the point gas hold-up values. It has been shown that SVR-based model for the bubble column reactor can be potentially useful for online prediction and monitoring of the point gas hold-up for different sparging conditions. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Bubble column; Gas hold-up; LDA; Recurrence quantification analysis (RQA); Support vector regression (SVR)

Two-phase flow in minichannels: hydrodynamics, pressure drop, and residence time distribution - Kulkarni, A. A.; Kalyani, Vishwanath S. (Industrial & Engineering Chemistry Research, 2009)
Two-phase flow in mini-channels (1 mm x 1.5 mm x 430 mm and 1.5 mm x 0.5 mm x 430 mm serpentine channel geometry) made in different materials (SS 316, PMMA and Teflon) was studied at different flow rate ratio (0.66, 1.0 and 1.56) of the two immiscible fluids. A dual syringe pump was used to pump the fluids (air-water and water-kerosene) through the channels. For characterization of the two phase flow, experiments were carried out to measure the slug size distribution and relevant hydrodynamic properties, pressure drop across a single serpentine unit (i.e., one sinusoidal unit that includes two 180 degrees return bends connected by a straight portion of 20 mm) and also the residence time distribution of water. In all the cases, the effect of material of fabrication on the hydrodynamics was significant. Apart from flow rates and flow rate ratio of the two fluids, the slug size distribution was seen to have a strong effect of the channel orientation (vertical, horizontal) and also the flow direction (up-flow and down-flow). In the RTD studies, the response curve observed at the end of the channel was significantly different than the published literature. The reasons for such observations are discussed in detail.

Continuous flow synthesis of functionalized silver nanoparticles using bifunctional biosurfactants - Kumar, D. V. Ravi; Kasture, Manasi; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad; Kulkarni, A. A. (Green Chemistry, 2010)
Silver nanoparticles were synthesized by continuous flow methods using biosurfactants, namely, oleic acid sophorolipid (OASL) and stearic acid sophorolipid (SASL). Both the sophorolipids can act as reducing and capping agents. The effect of temperature on the completion of nanoparticle formation and the particle growth dynamics (size) were studied in batch mode. While the completion of the reaction using oleic acid sophorolipid needed 20 min, only 5 min were required with the stearic acid sophorolipid as capping and reducing agent. Hence all the continuous flow experiments were carried out using the stearic acid sophorolipid. The continuous flow synthesis of silver nanoparticles was carried out in a stainless steel helical coil and also in a spiral polymeric minichannel reactor. The DLS results show that higher flow rate leads to the formation of bigger and polydisperse particles because of incomplete reactions. Higher residence time allowed the completion of reaction leading to spherical, small and monodisperse particles.

Continuous flow multipoint dosing approach for selectivity engineering in sulfoxidation - Kulkarni, A. A.; Nivangune, N. T.; Joshi, Rohini R.; Joshi, Ramesh A. (Organic Process Research & Development, 2013)
A continuous synthesis approach with multipoint dosing of one of the reagents is demonstrated for the synthesis of sulfoxide compounds such as proton pump inhibitors. Use of multipoint dosing of the oxidizing agent helped to minimize the possibility of over-oxidation leading to sulfone. Different oxidizing agents were used, and the effect of various parameters (viz. mole ratio of sulfide to oxidizing agent, temperature, residence time, concentration of oxidizing agent, etc.) on the yield of the desired sulfoxide compound was studied. Single-point and multipoint dosing approaches of the oxidizing agent were used for the most promising set of parameters. The performance was compared in terms of conversion of sulfide and the selectivity of the desired sulfoxide. Numbering up approach was used to produce the sulfoxide in a relatively large quantity at laboratory scale with complete conversion and over 99% selectivity for the sulfoxide.

Impinging jet micromixer for flow synthesis of nanocrystalline MgO: role of mixing/impingement zone - Kumar, D. V. Ravi; Bhagavatula L. V. Prasad; Kulkarni, A. A. (Industrial & Engineering Chemistry Research, 2013)
Continuous flow synthesis of nanomaterials via sol-gel process using microreactors has not received much attention. For the synthesis of gels where the reaction time is of the order of few seconds to few tens of seconds, microchannel reactors are an excellent processing option. However since a `gel' does not `flow' easily, making it in a microchannel usually clogs the microchannel. We envisaged that by using an impinging jet micromixer, where the two reactants impinge and collide to form a mixing zone outside the micromixer, this problem could be circumvented. Here we report a successful implementation of continuous flow synthesis of metal oxides formed by the rapid sol-gel process taking the nanocrystalline MgO (NC-MgO) as a specific example. Furthermore, we clearly demonstrate that the nature of the mixing zone formed by the impinging jets governs the surface area of the product. Specific flow rate and impingement angle are identified that yield high surface area materials.

Surfactant-free synthesis of anisotropic gold nanostructures: can dicarboxylic acids alone act as shape directing agents? - Kumar, D. V. Ravi; Kumavat, S. R.; Chamundeswari, V. N.; Patra, Partha Pratim; Kulkarni, A. A.; Bhagavatula L. V. Prasad (RSC Advances, 2013)
The present study describes the synthesis of gold nanostructures using different dicarboxylic (viz. oxalic, malonic, succinic, glutaric and adipic) acids as reducing agents in the absence of any other additives or surfactants. Various anisotropic structures such as kites, tadpoles, triangular/hexagonal plates, and twinned particles were seen to evolve depending on the molar ratio of dicarboxylic acid to HAuCl4 used. It was also demonstrated that gold nanostructure formation is hampered as the chain length/distance between two carboxylic acid groups increases. Among the various structures obtained the kite like structures displayed the largest surface enhanced Raman enhancement factors.

Microfluidic platform for continuous flow synthesis of triangular gold nanoplates - Kumar, D. V. Ravi; Kulkarni, A. A.; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2014)
A microfluidic platform for the continuous flow synthesis of triangular gold nanoplates with and without surfactants is developed. The temperature profile in the microchannel, residence time and composition have been studied to understand effect of these parameters on the yield of the triangular nanoplates and were optimized for obtaining maximum yield of triangles. The flow synthesis approach has been demonstrated where the Br- ions can be supplied to the reaction mixture either from the surfactant viz. Cetyl trimethylammonium bromide (CTAB) or even from HBr. Apart from the Br- ions, the temperature gradient at the inlet of the continuous flow reactor is one of the key parameter that affects the yield of the triangular nanoplates. Finally we establish that with a right combination of the controlling parameters abetter yield of the Au nanotriangles by flow methods can be achieved even in the absence of surfactant. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Au nanotriangles; Flow synthesis; microreactor; Nucleation kinetics; Surfactants

Continuous-flow nitration of o-xylene: effect of nitrating agent and feasibility of tubular reactors for scale-up - Sharma, Y.; Joshi, Ramesh A.; Kulkarni, A. A. (Organic Process Research & Development, 2015)
Continuous-flow nitration of o-xylene has been studied with different nitrating agents over a wide range of conditions for different parameters such as temperature, residence time, and concentrations. A nitrating mixture comprising sulfuric acid and fuming nitric acid was seen to yield higher selectivity for the isomer 1,2-dimethyl-3-nitrobenzene over the isomer 1,2-dimethyl-4-nitrobenzene and also a non-negligible quantity of dinitro derivatives of o-xylene. With only fuming nitric acid as the nitrating agent, the reaction was selective for 1,2-dimethyl-4-nitrobenzene over 1,2-dimethyl-3-nitrobenzene. Impurities mainly come from nitration of mononitro derivatives, and this occurs more from nitration of the 3-nitro isomer because of its higher reactivity with nitric acid. An economic analysis of the continuous-flow reactor for the production of 1,2-dimethyl-4-nitrobenzene at 100 and 500 kg/h in a jacketed tubular reactor showed that numbering-up is a more economical approach for higher production capacity. A combination of large- and small-sized tubes depending upon the relative rates of heat generation during a reaction will achieve more profit and a shorter payback period than having the entire reactor made of a single tube size.

Wet chemical synthesis of metal oxide nanoparticles: a review - Nikam, A. V.; Bhagavatula L. V. Prasad; Kulkarni, A. A. (Crystengcomm, 2018)
Metal oxide nanoparticles are an important class of nanomaterials that have found several applications in science and technology. Through wet chemical synthesis, it is possible to achieve selective surface structures, phases, shapes, and sizes of metal oxide nanoparticles, leading to a set of desired properties. Wet chemical synthesis routes allow fine tuning of the reaction conditions (temperature, concentration of substrate, additives or surfactants, pH, etc.) to afford the desired nanomaterials. In this review article, we highlight recent developments in the wet chemical synthesis of metal oxide nanoparticles to provide great control over the quality of the obtained nanomaterials. The review critically evaluates the different wet chemical methods for scalable production of metal oxide nanoparticles to satisfy the growing industrial demand for nanomaterials. Special attention is paid to continuous flow synthesis of metal oxide nanoparticles.

Quantitative comparison of strategies to delay clogging in straight capillaries - Pal, S.; Kulkarni, A. A. (Chemical Engineering Science, 2019)
It is challenging to achieve non-stop flow of a liquid-solid suspension through small channels as it eventually leads to clogging. This paper presents a quantitative comparison of four different techniques for enhancement of solid handling processes in microchannels of two different diameters. These techniques include dosing of the inert gas phase, dosing of the inert and immiscible liquid phase, and changing the wall wettability and multi-point injection, which, in principle, individually follow different mechanisms to delay clogging. An antisolvent based method for precipitation of salt was used to generate solid particles during flow. Clogging time at various flow rates from all the methods was measured and analysed. Irrespective of the method of delaying clogging, the scaling law of clogging time as a function of residence time was seen to remain unchanged. Among these methods, dosing of an inert, immiscible liquid has been identified as the most effective and robust method to delay clogging while enhancing transport of particles in segmented flow.

Telescoped sequence of exothermic and endothermic reactions in multistep flow synthesis - Sharma, Y.; Nikam, A. V.; Kulkarni, A. A. (Organic Process Research and Development, 2019)
A multistep sequential flow synthesis of isopropyl phenol is demonstrated, involving 4-step exothermic, endothermic, and temperature sensitive reactions such as nitration, reduction, diazotization, and high temperature hydrolysis. Nitration of cumene with fuming nitric acid produces 2- and 4-nitrocumene which are converted into respective cumidines by the hydrogenation using Pd/Ni catalyst in H-cube with gravity separation. Hydrolysis of in situ generated diazonium salts in the boiling acidic conditions is carried out using integration of flow and microwave-assisted synthesis. 58% of 4-isopropyl phenol was obtained. The sequential flow synthesis can be applied to synthesize other organic compounds involving this specific sequence of reactions.

Assessing the impact of deviations in optimized multistep flow synthesis on the scale-up (vol 5, pg 838, 2020) - Sharma, M. K.; Raval, J.; Ahn, Gwang-Noh; Kim, Dong-Pyo; Kulkarni, A. A. (Reaction Chemistry & Engineering, 2021)

Heterogeneous nucleation in citrate synthesis of AgNPs: effect of mixing and solvation dynamics - Deshpande, J. B.; Chakrabarty, S.; Kulkarni, A. A. (Chemical Engineering Journal, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">The heterogeneity issues in silver nanoparticle nucleation (Lee-Meisel route) have been investigated. The final polydispersity and sphericity of the nanoparticles in the Lee-Meisel scheme are shown to depend upon the early time dynamics of silver-citrate complexation. The formation of macromolecular intermediary complexes in the early stages of the reaction is visualized based on online DLS data, TEM analysis, and the mass balances of silver and citrate ions. The reversible complexation between citrate ions and silver citrate is shown to be the limiting step that governs the directional growth of the nanoparticles. The dynamics of the complexation of citrate are seen to form a very rapid step and intense mixing was required for the complexation to happen uniformly across the reaction. This specific observation is also confirmed from the MD simulations. Thus, to get particles of high sphericity, irrespective of the reaction concentration, temperature, or reactor geometry, the mixing time should be <4 s and <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Da<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> ~ 0.1. Optimal mixing conditions for isotropic growth are suggested based on the reaction kinetics and are also demonstrated with experimental evidence.

Assessment of a multipoint dosing approach for exothermic nitration in CSTRs in series - Mule, G. M.; Kulkarni, S.; Kulkarni, A. A. (Reaction Chemistry & Engineering, 2022)
The exothermic aromatic nitration of a biaryl compound is studied using various configurations of CSTRs in series. The relative rates of heat generation and heat removal in different configurations are compared to identify safer options while taking scale-up-related decisions. The effects of different parameters on the steady-state temperatures of the CSTRs are demonstrated through simulations. The use of multipoint dosing in three different CSTRs of increasing volume in series was compared with the use of standard CSTRs of equal volume in series. The distribution of the nitrating agent in three different CSTRs in series helped to distribute the heat duty and thereby helped maximise the throughput almost 2.4-fold when compared with a conventional approach based on the co-addition of all the reactants in the first CSTR. Various feed combinations were studied, and suitable designs that fall within the safe operating range of CSTRs for highly exothermic reactions are given.